Students’ Perception of Artificial Intelligence (AI) Usage in Academic Writing - Purnomo, Dinda Retno Putri; Zulfi Zumala Dwi Andriani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the perceptions of English Education students regarding the use of Artificial Intelligence (AI) in Academic Writing. Utilizing a qualitative research design, the investigation was conducted through semi-structured interviews by FGD (Focus Group Discussion) and questionnaires among students from the English Education Department at University “A” in Banyuwangi, East Java. Findings reveal that AI considerably enhances students’ efficiency and writing quality by offering tools that assist with grammar correction, reference finding, and generating ideas. The results of the survey indicate that ChatGPT is the most popular platform, with over 90% of students using it to produce writing assignments. Students reported improved confidence in their writing, attributing these advancements to AI platforms such as ChatGPT, Grammarly, and Gama. However, concerns regarding the potential misuse of AI, such as plagiarism and over-reliance were also highlighted. The study underscores the necessity for digital literacy in effectively integrating AI into academic practices. Overall, the findings suggest that while AI significantly supports academic writing, its ethical usage is crucial to maintaining academic integrity.